2018
DOI: 10.1136/postgradmedj-2018-135638
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in heart failure

Abstract: Exercise training (ET) in heart failure (HF) has long been established as an important part of HF care. ET is known to improve quality of life and functional capacity in a number of ways. Despite its proposed benefits, evidence supporting its routine inclusion in standard rehabilitation programme is at times conflicting, partly because of the significant heterogeneity present in available randomised controlled trials. There is lack of evidence with regard to the duration of the overall benefit, the optimal exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…[3][4][5][6][7] Physical exercise in experimental heart failure attenuated ventricular dilation, cardiac dysfunction, increased passive stiffness, myocyte hypertrophy, myocardial fibrosis, myocyte calcium handling changes and mitochondrial dysfunction. [8][9][10][11][12][13] However, as most benefits of exercise have been described in experimental models of myocardial infarction-induced heart failure, [14][15][16][17] the effects of exercise during sustained LV pressure-overload remains poorly understood. In fact, studies performed in this experimental model have returned controversial results.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Physical exercise in experimental heart failure attenuated ventricular dilation, cardiac dysfunction, increased passive stiffness, myocyte hypertrophy, myocardial fibrosis, myocyte calcium handling changes and mitochondrial dysfunction. [8][9][10][11][12][13] However, as most benefits of exercise have been described in experimental models of myocardial infarction-induced heart failure, [14][15][16][17] the effects of exercise during sustained LV pressure-overload remains poorly understood. In fact, studies performed in this experimental model have returned controversial results.…”
mentioning
confidence: 99%
“…However, in disease state, a clinical study showed that physical exercise may impair cerebral perfusion in patients with chronic heart failure because of their reduced ability to increase CO [55]. Further investigation to disclose the impact of exercise on cerebral perfusion shortly after MI and before heart failure establishment is warranted especially when physical exercise is currently considered a standard rehabilitation program post-MI [56,57]. …”
Section: Discussionmentioning
confidence: 99%